Minimum wages and changing wage inequality in India - Saloni Khurana; Kanika Mahajan; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Using nationally representative data on employment and earnings, this paper documents a fall in wage inequality in India over the last two decades. It then examines the role played by increasing minimum wages for the lowest skilled workers in India in contributing to the observed decline. Exploiting regional variation in changes in minimum wages over time in the country, we find that an increase in minimum wages by one per cent led to an increase in wages for workers in the lowest quintile by 0.17 per cent. This effect is smaller at upper wage quintiles and insignificant for the highest wage quintile. Counterfactual wage estimations show that the increases in minimum wages explain 26 per cent of the decline in wage inequality. These findings underscore the important role played by rising minimum wages in reducing wage disparities in India.
Keywords: J31; J38; 330; minimum wages; wage inequality; India; employment